2022
DOI: 10.1038/s41467-022-30515-0
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 gRNA activity depends on free energy changes and on the target PAM context

Abstract: A major challenge of CRISPR/Cas9-mediated genome engineering is that not all guide RNAs (gRNAs) cleave the DNA efficiently. Although the heterogeneity of gRNA activity is well recognized, the current understanding of how CRISPR/Cas9 activity is regulated remains incomplete. Here, we identify a sweet spot range of binding free energy change for optimal efficiency which largely explains why gRNAs display changes in efficiency at on- and off-target sites, including why gRNAs can cleave an off-target with higher e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 63 publications
(105 reference statements)
2
26
0
Order By: Relevance
“…Although we predicted the gRNAs with three SNPs would have a negative effect on CasRx cleavage, we found that these guides significantly improved its nuclease activity in both RdRp and N compared to the guides without mismatches ( p = 0.0278 and p = 0.0304, respectively). Recent work using an energy-based model with Cas9 has found that interactions between gRNA and the targeted DNA may influence cleavage activity, resulting in Cas9 cleaving off-target sites with higher efficiency than on-target sites [ 22 , 23 ]. It is possible there is a similar interaction between gRNAs and targeted RNA when Cas13 is used, but this should be further elucidated in future work using a robust number of gRNA sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Although we predicted the gRNAs with three SNPs would have a negative effect on CasRx cleavage, we found that these guides significantly improved its nuclease activity in both RdRp and N compared to the guides without mismatches ( p = 0.0278 and p = 0.0304, respectively). Recent work using an energy-based model with Cas9 has found that interactions between gRNA and the targeted DNA may influence cleavage activity, resulting in Cas9 cleaving off-target sites with higher efficiency than on-target sites [ 22 , 23 ]. It is possible there is a similar interaction between gRNAs and targeted RNA when Cas13 is used, but this should be further elucidated in future work using a robust number of gRNA sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Our data further showed that mismatches at the two upstream PAM proximal position (N19 and N20) were more tolerated than other nucleotides of the seed region. This site-dependent effect could be explained by our recent binding energy model about the effect of sliding PAMs on CRISPR-Cas9 specificity 67 . Indeed, when performing benchmarking of the different CRISPR-Cas9 off-target prediction tools with our data, our results also showed that energy-based predictors out-performed other tools in their accuracy of predicting true off-targets.…”
Section: Discussionmentioning
confidence: 91%
“…10.1101/2020.05.20.103614). Recently, we further demonstrated that this surrogate library approach can be used to evaluate PAM compatibility in human cells 67 . We anticipate that SURRO-seq could be adapted to evaluate off-targets of other DNA editing RGN systems, including prime editing 68 .…”
Section: Discussionmentioning
confidence: 97%
“…We found that PAM-flexible dCas9 variants exhibited weaker CRISPRi-based gene repression compared to dCas9 (Figure 3B). One possible explanation for this behavior follows from the observation that increasing PAM promiscuity reduces affinity towards NGG PAMs (Corsi et al, 2022; Hu et al, 2018; Legut et al, 2020; Nishimasu et al, 2018; Walton et al, 2020). This reduced PAM-binding affinity could allow RNA polymerase to more readily displace the CRISPRi complex.…”
Section: Discussionmentioning
confidence: 99%